Monte Carlo simulations to support start-up and treatment planning of scanned proton and carbon ion therapy at a synchrotron-based facility - Parodi, Katia; Mairani, Andrea; Brons, Stephan; Hasch, Bernhard Georg; Sommerer, Florian; Naumann, Jakob; Jäkel, Oliver; Haberer, Thomas; Debus, Jürgen (Physics in medicine and biology, 2012)
Reliable treatment planning of highly conformal scanned ion beam therapy demands accurate tools for the determination and characterization of the individual pencil-like beams building up the integral dose delivery and related mixed radiation field. At present, clinically practicable inverse treatment planning systems (TPSs) can only rely on fast-performing analytical algorithms. However, the rapidly emerging though more computationally intensive Monte Carlo (MC) methods can be employed to complement analytical TPS, e.g., via accurate calculations of the input beam-model data, together with a considerable reduction of the measuring time. Here we present the work done for the application of the FLUKA MC code to support several aspects of scanned ion beam delivery and treatment planning at the Heidelberg Ion Beam Therapy Center (HIT). Emphasis is given to the generation of the accelerator library and of experimentally validated TPS input basic data which are now in clinical use for proton and carbon ion therapy. Additionally, MC dose calculations of planned treatments in water are shown to represent a valuable tool for supporting treatment plan verification in comparison to dosimetric measurements. This paper can thus provide useful information and guidelines for the start-up and clinical operation of forthcoming ion beam therapy facilities similar to HIT.
Gesehen am 12.06.2018